PERCEPTION OF FLOOD RISK COPING AND ADAPTIVE STRATEGIES OF RESIDENTS: EXAMPLE OF MUSHIN, NIGERIA - Yoade, Adewale Olufunlola; Onifade, Victor; Olatunji, S.A.; Husseni, M.A. (Journal of Surveying, Construction and Property, 2023)
The study perception of flood risk coping and adaptive strategies of residents in Mushin, Lagos State, Nigeria. Both primary and secondary data were utilized for this study. Personal interview entailed holding discussion with residents in the study area and also staffs from the relevant agencies in charge of the environment, especially a staff from Lagos State Ministry of Environment and Lagos State Physical Planning and Development Authority (LASSPDA). The research population for this study was number of buildings in the selected drought prone areas of the community through reconnaissance survey. A total of 429 buildings was counted using Google Earth map. The number of buildings on each street within the study area and the number of questionnaires distributed in the street, using a systematic random distribution technique. Therefore, a total number of 196 questionnaires represent the sample size of the study area, since all areas cannot be covered due to constraint of time. Data gathered from field survey was examined using descriptive and inferential statistics. The study therefore recommends that there must try as much harder to increase flood control and management, disaster management must be put in place, readily available to tackle flood issues, climate change reduction and adaptation initiatives, so as to increase the flexibility capabilities of our environment and its components.